Prospect of aerogels as desiccant materials: Possibilities and challenges - Asim N.; Badiei M.; Fudholi A.; Razali H.; Mohammad M.; Samsudin N.A.; Akhtaruzzaman Md.; Amin N.; Sopian K. (Begell House Inc., 2023)
Aerogels; Agricultural robots; Industrial wastes; Adsorption of water vapors; Current limitation; High surface area; Porous nanostructures; Research studies; Driers (materials)